The Phenomenon of Book Burial by Narrators and its Impact on the Narrator and Narration: An Inductive and Analytical Study - Alasasmeh , Adel Harb Bashir (Dirasat: Shari’a and Law Sciences, 2020)
The study aims to find out the reasons and motives that led the narrator to bury his books; which tired and stayed up for the sake of collecting their narrations, achieving them and presenting them to the narrations of trust, and revising them from errors and illusion, and to know the narrators who buried their books openly verbally, and to know the impact of burying books and to know the impact of burying books, and to show that it is not a general approach; it is special cases that are worth nothing compared to a huge amount of narrators. The study used the inductive analytical method by studying the phenomenon of book Burial and its motives for narrators. The study came to the following conclusions: restraint is a prerequisite for accepting the narrator’s novel; because justice alone is not enough, judging narrators requires accuracy, objectivity, and great effort, that the area and size of burial and execution of books, in all its forms, constitutes a very small percentage. The study recommends the importance of seeking excuses for narrators who buried their books by knowing their motives, and not judging their novel in general, and also recommends the importance of highlighting the narrator’s environment, curriculum, school, and others, to identify the features of geography, history during periods, and their impact on narrators and the novel.